Derivatives, pricing efficiency and gharar. Evidence on embedded options in Malaysia - Haron, Razali (2014)
The use of derivatives as risk management instrument has accelerated rapidly where financial instruments like options, forward, future and swaps have been widely used to manage risks. Regardless of its extensive usage, the use of derivatives as risk management tools receives differing arguments among the Muslim scholars. Focusing on the use of options contract, despites its economic benefits of hedging activities they are also used for speculative purposes that contravene with the Maqasid al Shariah. The resolution of Islamic Fiqh Academy, Jeddah No (63/1/7) under the financial markets claims that they cannot categorize the currently applied option contracts under any one of the Shariah nominate contracts and the nature of the contemporary options is that it is neither a sum of money nor a utility or a financial right which may be waived, thus not permissible in Shariah.” Options are also objected to because of the payment of a premium, and conditional options are not allowed in currency exchanges. Options are also accused of containing the element of gharar which is prohibited in fiqh muamalat. Therefore, the objective of this study is to investigate the existence of one of the prohibited elements which is gharar in one of the financial innovations, embedded options (equity warrants) since most Islamic scholars reject the conventional instrument on the basis of gharar and that this option is transacted for speculative gains. This study examined the existence of gharar element in the pricing especially in the case of mispricing by employing the Black Scholes Option Pricing Model (BSOPM). 183 outstanding equity warrants understudy within the period of six years from January 2006 to December 2012 were examined and there seemed to be mispricing in reference with their theoretical values indicating inefficiency in the Malaysian market. Mispricing of this instrument in the Malaysian market indicates speculative activities which are prohibited in Islam. Speculation may contain gharar (uncertainty) and maysir (gambling) and Islam forbids these because they may result in wealth accumulation at the expense of other parties’ jahl (ignorance). This activity violates the concept of adl (justice), does not serve the concept of maslahah (public interest) and does not follow the Maqasid al Shariah. The main contribution of this study is that it provides empirical evidence which is very much lacking in the study of options in Islamic Finance. The existence of gharar is empirically and statistically evidenced thus is hoped to shed some lights to the scholars and be able to come to a consensus on this unresolved fiqh issue on the permissibility status of this financial instrument. This empirical evidence may act as a catalyst to those responsible in the Islamic Financial product innovations to come up with a risk management instrument which are undoubtedly Shariah compliant and do not violate the Maqasid al Shariah and most importantly can perform at par if not far better with its conventional counterparts.